Analysis of the Temperature Detection System: Impact and Challenges - Muhammad Ahmad Baballe; Mukhtar Ibrahim Bello (Journal of Telecommunication Control and Intelligent System, 2021)
Analysis of the Temperature Detection System: Impact and Challenges